2022
DOI: 10.1108/intr-05-2021-0310
|View full text |Cite
|
Sign up to set email alerts
|

How can we achieve better e-Learning success in the new normal?

Abstract: PurposeThis study aims to propose and validate a model for e-Learning success based on students’ experiences in the “new normal.” To achieve this goal, this study focused on answering three research questions: (1) What are the students’ experiential factors that impact e-Learning? (2) How do these experiential factors affect e-Learning success? (3) In what ways does a multimethod provide a comprehensive perspective and an in-depth understanding of students’ e-Learning experiences in the new normal?Design/metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 90 publications
0
10
0
1
Order By: Relevance
“…Shiau et al (2023) propose an extended model to explain user behavior regarding the facial recognition payment systems in China. Kim et al (2023a) also articulate the importance of online interaction during the e-Learning process.…”
Section: Special Issue Process and Final Articlesmentioning
confidence: 99%
See 4 more Smart Citations
“…Shiau et al (2023) propose an extended model to explain user behavior regarding the facial recognition payment systems in China. Kim et al (2023a) also articulate the importance of online interaction during the e-Learning process.…”
Section: Special Issue Process and Final Articlesmentioning
confidence: 99%
“…Special issue articles for the four components Contactless technology artifacts: All articles in this special issue cover diverse types of contactless technology artifacts such as AR-based service applications (Yin and Hsu, 2023), AR for shopping (Riar et al, 2023), healthcare and fitness apps (Zhu et al, 2023), self-service kiosks and food-ordering mobile apps (Lee et al, 2023), facial recognition payment (Shiau et al, 2023), digital tools (e.g. DingTalk and WeChat) (Zhang et al, 2023) and e-Learning systems (Kim et al, 2023a). Particularly, five articles investigated the interactions between users and contactless technology artifacts and showed that contactless technology artifacts positively affect the acceptance and (continuous) intention to use, although their research contexts are different (Kim et al, 2023a;Lee et al, 2023;Shiau et al, 2023;Yin and Hsu, 2023;Zhu et al, 2023).…”
Section: Special Issue Process and Final Articlesmentioning
confidence: 99%
See 3 more Smart Citations